Emergency remote teaching during COVID-19 crisis: An analysis of EFL students’ engagement in Aceh - M. Amin, Fakhrurrazi; Zulfitri, Zulfitri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
To prevent the spread of the coronavirus (Covid-19) and its pandemic, emergency remote teaching must be implemented. This has brought significant problems and difficulties for students due to this unusual circumstance, EFL students must learn to adapt their abilities. Because of the widespread use of technology in education, the quick transition to complete online learning necessitates some adjustment. EFL students must be able to handle online learning that is performed through technology integration and utilizing technological tools they have never used before in a short period of time. In response to emergency remote teaching, this study examined how engaged EFL students are, as well as their perceptions of such engagement. One hundred ninety-one students from four state Islamic universities in Aceh filled out an online questionnaire adapted from McColskey (2012). Both descriptive and thematic methods were used to analyze the data. EFL students demonstrated their level of engagement in all three categories of engagement: behavioral, emotional, and cognitive engagement. Positive responses and feelings of satisfaction were shown during emergency remote teaching. It indicates that EFL students have a better grasp of how to use technology in education. It is essential to constantly enhance their skills and have enough equipment and infrastructure to facilitate online learning.